Synthesis of qualitative research studies regarding the factors surrounding UK critical care trial infrastructure. Issue 12 (22nd December 2019) - Pattison, Natalie; Arulkumaran, Nishkantha; O'Gara, Geraldine; Connolly, Bronwen; Humphreys, Sally; Walsh, Tim; Hopkins, Philip; Dark, Paul
Abstract : Conducting clinical trials in critical care is integral to improving patient care. Unique practical and ethical considerations exist in this patient population that make patient recruitment challenging, including narrow recruitment timeframes and obtaining patient consent often in time-critical situations. Units currently vary significantly in their ability to recruit according to infrastructure and level of research activity. Aim: To identify variability in the research infrastructure of UK intensive care units and their ability to conduct research and recruit patients into clinical trials. Design: We evaluated factors related to intensive care patient enrolment into clinical trials in the UK. This consisted of a qualitative synthesis carried out with two datasets of in-depth interviews (distinct participants across the two datasets) conducted with 27 intensive care consultants (n=9), research nurses (n=17) and trial coordinators (n=1) from 27 units across the UK. Primary and secondary analyses of two datasets (one dataset had been analysed previously) were undertaken in the thematic analysis. Findings: The synthesis yielded an overarching core theme of normalising research, characterised by motivations for promoting research and fostering research-active cultures within resource constraints, with six themes under this to explain the factors influencing critical care research capacity: organisational, human, study, practical resources, clinician and patient/family factors. There was a strong sense of integrating research in routine clinical practice, and recommendations are outlined. Conclusions: The central and transferable tenet of normalising research advocates the importance of developing a culture where research is inclusive alongside clinical practice in routine patient care and is a requisite for all healthcare individuals from organisational to direct patient contact level.